2010
DOI: 10.4236/health.2010.27116
|View full text |Cite
|
Sign up to set email alerts
|

Alternations in salivary glucose during ramadan fasting

Abstract: During the holly month of Ramadan, Muslims fast every day from dawn to sunset. Although the effect of Ramadan fasting on general health has been widely studied, the impact of fasting on oral health and possible changes in salivary biochemicals, such as glucose, has not received much attentiom. The aim of our study was to evaluate the influence of fasting on the level of glucose in the saliva of healthy individuals. Salivary glucose was measured using an enzymatic method based on oxidation of glucose by glucose… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
39
0

Year Published

2015
2015
2021
2021

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 10 publications
(39 citation statements)
references
References 9 publications
0
39
0
Order By: Relevance
“…5 We have previously found that the biochemistry of human saliva is altered in response to external and internal factors such as smoking, 6 vegetarian diet, 7 peptic ulcer 8 and Ramadan fasting. 9 Other investigators have shown that in vitro exposure to cigarette smoke could significantly decrease biological activity of some enzymes, both in plasma and in saliva. 10,11…”
Section: Introductionmentioning
confidence: 99%
“…5 We have previously found that the biochemistry of human saliva is altered in response to external and internal factors such as smoking, 6 vegetarian diet, 7 peptic ulcer 8 and Ramadan fasting. 9 Other investigators have shown that in vitro exposure to cigarette smoke could significantly decrease biological activity of some enzymes, both in plasma and in saliva. 10,11…”
Section: Introductionmentioning
confidence: 99%
“…Other than that, some of the respondents are removable orthodontic appliances users that had regularly scaling treatment. Another research concluded by Sariri about alternative glucose saliva during Ramadhan fasting [18] explained that even though Ramadhan fasting affected saliva glucose, it would not affect glucose function in healthy human's saliva, since the concentration of glucose saliva depended on their intake during fasting. Normal saliva function was considered important for healthy oral mucose maintenance.…”
Section: Resultsmentioning
confidence: 99%
“…16 While increased blood glucose may lead to higher levels of salivary glucose, 12 a decrease in mean glucose concentration is seen in the saliva of fasting subjects when compared to the control group. 17 A significant correlation was seen between postprandial serum and salivary glucose levels in both diabetics and nondiabetics (P < .001) in the study conducted by Gupta et al 21 Self monitoring of blood glucose has made the task of monitoring diabetes less burdensome. However, it's many disadvantages (painful, inconvenient, messy, embarrassing, expensive) cause patients to find the testing distressing.…”
Section: Introductionmentioning
confidence: 93%
“…15 Saliva is an organic fluid and is made up of many constituents like glucose and amylase 16 and is the first biological fluid to be affected by any change in eating habits or any environmental or physical changes. 17 Glucose moves through membranes of blood vessels as it is a small molecule and then passes from the blood plasma via gingival sulcus to the gingival fluid, and reaches the saliva. 18 Diabetes mellitus is known to alter salivary composition and function which disrupts the homeostasis of the oral cavity and makes it more prone for oral diseases.…”
Section: Introductionmentioning
confidence: 99%